PERCEPTION OF THE FAMILY CAREGIVER REGARDING PROBLEMS FACED BY CHILDREN IN RELATION TO THEIR DIAGNOSIS OF HIV/AIDS - Márcia Marcos de Lara; Giovana Calcagno Gomes; Camila Magroski Goulart Nobre; Bianca Contreira de Jung; Aline Rodrigues Costa; Eloisa da Fonseca Rodrigues (Universidade Federal do Paraná, 2017)
This study aimed to investigate the perception of the family caregiver regarding the problems faced by the child in relation to her diagnosis of Human Immunodeficiency Syndrome. A qualitative, exploratory and descriptive study was undertaken in a Day Hospital which is a center of excellence in the South of Brazil, in the second semester of 2014. The participants were 10 family caregivers of children attended in the service. The data were collected through semistructured interviews and underwent content analysis. The results emphasized the following as problems faced by the family caregiver: the need for frequent inpatient treatment, being the only person with the virus in the family, suffering prejudice within the family and at school, presenting growth delays and psychological problems. It is necessary for nurses to take responsibility for our educational role with these families so as to help them develop effective strategies for caring for the child.